2020
DOI: 10.13189/ujer.2020.081044
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perception toward Online Education in a State College in the Philippines during the Coronavirus Disease 19 (COVID-19) Pandemic

Abstract: This research determined the perception toward online education among faculty in a State College in the Philippines. This study used a descriptive online survey involving a sample of 27 faculty members. Statistical tools employed were descriptive statistics, Mann-Whitney U test, and Kruskal-Wallis test. Research findings indicated that the majority of faculty had intermediate computer competency and had no training in online teaching, with only a few having a very stable internet connection. Faculty considered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 20 publications
(25 reference statements)
6
126
0
8
Order By: Relevance
“…Nghiên cứu của Talidong và Toquero [6] cho thấy giáo viên Phi-líp-pin tương đối lo lắng vì không được đi dạy, cuộc sống bị đảo lộn nhiều và họ thường sử dụng các mạng xã hội để theo dõi diễn biến dịch, liên lạc với đồng nghiệp, người thân. Cũng tại Phi-líp-pin, nghiên cứu của Moralista và Oducado [7] thực hiện với 27 giảng viên đại học trong giai đoạn xảy ra đại dịch Covid-19 cho thấy giảng viên chưa hoàn toàn ủng hộ việc dạy trực tuyến dù đây là hình thức dạy bắt buộc trong giai đoạn này. Một số nghiên cứu khác trong giai đoạn này khẳng định tầm quan trọng của việc cần có thiết kế bài giảng, hoạt động học tập trực tuyến phù hợp đảm bảo sự kết hợp tốt giữa yếu tố công nghệ và chuyên môn, tận dụng các hình thức tương tác đồng thời, không đồng thời trên môi trường mạng và tìm ra phương thức linh hoạt bù đắp thiệt hại của sinh viên khi không được trực tiếp đến lớp [8,9].…”
Section: đặT Vấn đề *unclassified
See 2 more Smart Citations
“…Nghiên cứu của Talidong và Toquero [6] cho thấy giáo viên Phi-líp-pin tương đối lo lắng vì không được đi dạy, cuộc sống bị đảo lộn nhiều và họ thường sử dụng các mạng xã hội để theo dõi diễn biến dịch, liên lạc với đồng nghiệp, người thân. Cũng tại Phi-líp-pin, nghiên cứu của Moralista và Oducado [7] thực hiện với 27 giảng viên đại học trong giai đoạn xảy ra đại dịch Covid-19 cho thấy giảng viên chưa hoàn toàn ủng hộ việc dạy trực tuyến dù đây là hình thức dạy bắt buộc trong giai đoạn này. Một số nghiên cứu khác trong giai đoạn này khẳng định tầm quan trọng của việc cần có thiết kế bài giảng, hoạt động học tập trực tuyến phù hợp đảm bảo sự kết hợp tốt giữa yếu tố công nghệ và chuyên môn, tận dụng các hình thức tương tác đồng thời, không đồng thời trên môi trường mạng và tìm ra phương thức linh hoạt bù đắp thiệt hại của sinh viên khi không được trực tiếp đến lớp [8,9].…”
Section: đặT Vấn đề *unclassified
“…Lackey [26] cho rằng việc bồi dưỡng cho giảng viên dạy trực tuyến sẽ làm tăng sự hài lòng của họ cho dù việc dạy trực tuyến là bắt buộc hay tự nguyện. Những yếu tố liên quan đến công nghệ, bao gồm tính tiện lợi, dễ sử dụng của phần mềm và hiệu quả của một khóa học trực tuyến cụ thể [7,27].…”
Section: Các Yếu Tố Tác độNg đếN Sự Hài Lòng Của Giảng Viên Khi Dạy Tunclassified
See 1 more Smart Citation
“…With the three types of knowledge: awareness, how-to, and principles, an individual must absorb information about online learning (Rogers, 2003, p. 172). Moralista and Oducado (2020) noted that faculty typically felt online work to lead to more academic dishonesty, which may result in them being hesitant to participate. This is when those individuals must be ushered into the persuasion stage.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It also showed high score, it was 80-100 from the maximum score 100. Another study toward the perception of online came from Moralista, Rome,. & Oducado (2020) showed that the faculty examines to embrace the educational challenges and they have to improve skill through training and development.…”
Section: Introductionmentioning
confidence: 99%